The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1128/jb.01168-06
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniaeDivIVA: Localization and Interactions in a MinCD-Free Context

Abstract: To clarify the function of DivIVA in Streptococcus pneumoniae, we localized this protein in exponentially growing cells by both immunofluorescence microscopy and immunoelectron microscopy and found that S. pneumoniae DivIVA (DivIVA SPN ) had a unique localization profile: it was present simultaneously both as a ring at the division septum and as dots at the cell poles. Double-immunofluorescence analysis suggested that DivIVA is recruited to the septum at a later stage than FtsZ and is retained at the poles aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
128
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(142 citation statements)
references
References 51 publications
(118 reference statements)
13
128
1
Order By: Relevance
“…Markerless deletions of the division genes, mapZ (alternative name, locZ) and divIVA, fused short (20-amino acid) stretches from the beginning and end of the genes to maintain possible translational coupling (see Tables S1 and S2). The phenotypes of the markerless ⌬mapZ and ⌬divIVA mutants were similar to those reported previously for other mapZ and divIVA mutants (41)(42)(43).…”
Section: Methodssupporting
confidence: 73%
“…Markerless deletions of the division genes, mapZ (alternative name, locZ) and divIVA, fused short (20-amino acid) stretches from the beginning and end of the genes to maintain possible translational coupling (see Tables S1 and S2). The phenotypes of the markerless ⌬mapZ and ⌬divIVA mutants were similar to those reported previously for other mapZ and divIVA mutants (41)(42)(43).…”
Section: Methodssupporting
confidence: 73%
“…FtsA, together with FtsZ, is one of the earliest proteins to localize at the division sites, whereas DivIVA arrives somewhat later (43,44). Interestingly, we now have shown that StkP phosphorylates DivIVA and FtsA in vitro (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…As in the model organisms E. coli and B. subtilis, FtsZ and FtsA are the first proteins to arrive at midcell in S. pneumoniae and form the Zring before cell division initiates (47,48). Once formed, the Zring recruits the later cell-division proteins such as the membrane connectors, DivIVA, and the enzymes required for septal cell-wall synthesis [PBPs, likely PBP2x and PBP1a (4,43)]. However, before septation can proceed in oval cells such as S. pneumoniae, peripheral cell-wall synthesis must occur (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pneumococcal protein DivIVA is one of a number of membrane proteins that orchestrate and fine tune cell wall synthesis during septal growth and cell separation and localize to the division septum and to the poles of cocci (21,22). It has been proposed that DivIVA tunes the 2 modes of peptidoglycan (peripheral and septal) synthesis in pneumococci and is responsible for the cell's ovoid shape (22).…”
Section: Resultsmentioning
confidence: 99%